Depleted upconversion luminescence in NaYF4:Yb3+, Tm3+ nanoparticles via simultaneous two-wavelength excitation. Issue 27 (28th June 2017) - Zhang, Hongxin; Jia, Tianqing; Chen, Long; Zhang, Yuchan; Zhang, Shian; Feng, Donghai; Sun, Zhenrong; Qiu, Jianrong
Abstract : Depleted UCL in NaYF4 :Yb 3+, Tm 3+ UCNPs upon simultaneous excitation at 980 nm and 1550 nm is attributed to the STED process. Abstract : We report optical depletion of upconversion luminescence (UCL) in NaYF4 :Yb 3+, Tm 3+ nanoparticles excited simultaneously by 980 nm and 1550 nm lasers. The UCL intensity is greatly depleted, while the downshifted emission at 1210 nm is obviously enhanced. The disturbances of 1550 nm photons on energy transfer between Yb 3+ and Tm 3+, cross relaxation (CR), the thermal effect and the stimulated emission depletion (STED) process are qualitatively evaluated. Our investigations verify that the unexpected depletion phenomena are governed by the STED process. The power densities of the 980 nm and 1550 nm lasers are both less than 100 W cm −2, which will greatly reduce the thermal effect and damage and extend the applications of such nanomaterials. These results provide keen insights into controlling emission colors in optical processes, and offer potential applications in multicolor displays and STED nanoscopy.